Impact of spaceflight stressors on behavior and cognition: A molecular, neurochemical, and neurobiological perspective. (July 2022) - Desai, Rajeev I.; Limoli, Charles L.; Stark, Craig E.L.; Stark, Shauna M.
Abstract: The response of the human body to multiple spaceflight stressors is complex, but mounting evidence implicate risks to CNS functionality as significant, able to threaten metrics of mission success and longer-term behavioral and neurocognitive health. Prolonged exposure to microgravity, sleep disruption, social isolation, fluid shifts, and ionizing radiation have been shown to disrupt mechanisms of homeostasis and neurobiological well-being. The overarching goal of this review is to document the existing evidence of how the major spaceflight stressors, including radiation, microgravity, isolation/confinement, and sleep deprivation, alone or in combination alter molecular, neurochemical, neurobiological, and plasma metabolite/lipid signatures that may be linked to operationally-relevant behavioral and cognitive performance. While certain brain region-specific and/or systemic alterations titrated in part with neurobiological outcome, variations across model systems, study design, and the conspicuous absence of targeted studies implementing combinations of spaceflight stressors, confounded the identification of specific signatures having direct relevance to human activities in space. Summaries are provided for formulating new research directives and more predictive readouts of portending change in neurobiological function. Highlights: Neurocognitive consequences of exposure to spaceflight stressors were evaluated. Radiation, sleep deprivation, isolation and microgravity were critically reviewed. Lack of combined stressor studies was conspicuously absent. No common pathways/biomarkers relevant to functional CNS outcomes were uncovered. Recommendations for minimizing CNS risks of deep space exploration are provided.